Proteomic analysis and candidate allergenic proteins in Populus deltoides CL. “2KEN8” mature pollen - Zhang, Jin; Wu, Li-Shuan; Fan, Wei; Zhang, Xiao-Ling; Jia, Hui-Xia; Li, Yu; Yin, Ya-Fang; Hu, Jian-Jun; Lu, Meng-Zhu (Frontiers in Plant Science, 2015)
Proteomic analysis was used to generate a map of Populus deltoides CL. ‘2KEN8’ mature pollen proteins. By applying 2-D electrophoresis, we resolved 403 protein spots from mature pollen. Using the matrix-assisted laser desorption/ionization time time-of-flight/time-of-flight tandem mass spectrometry method, we identified 178 distinct proteins from 218 protein spots expressed in mature pollen. Moreover, out of these, 28 proteins were identified as putative allergens. The expression patterns of these putative allergen genes indicate that several of these genes are highly expressed in pollen. In addition, the members of profilin allergen family were analyzed and their expression patterns were compared with their homologous genes in Arabidopsis and rice. Knowledge of these identified allergens has the potential to improve specific diagnosis and allergen immunotherapy treatment for patients with poplar pollen allergy.